Modular Orthopaedic Tissue Engineering With Implantable Microcarriers and Canine Adipose-Derived Mesenchymal Stromal Cells - Simitzi, Chara; Vlahovic, Maja; Georgiou, Alex; Keskin-Erdogan, Zalike; Miller, Joanna; Day, Richard M. (Frontiers in Bioengineering and Biotechnology, 2020)
Mesenchymal stromal cells (MSC) hold significant potential for tissue engineering applications. Modular tissue engineering involves the use of cellularized ‘building blocks’ that can be assembled via a bottom-up approach into larger tissue-like constructs. This approach emulates more closely the complexity associated hierarchical tissues compared with conventional top-down tissue engineering strategies. The current study describes the combination of biodegradable porous PLGA microcarriers with canine adipose-derived MSC (cAdMSC) for use as implantable conformable building blocks in modular tissue engineering applications. Optimal conditions were identified for the attachment and proliferation of cAdMSC on the surface of the microcarriers. Culture of the cellularized microcarriers for 21 days in transwell insert plates under conditions used to induce either chondrogenic or osteogenic differentiation resulted in self-assembly of solid 3D tissue constructs. The tissue constructs exhibited phenotypic characteristics indicative of successful osteogenic or chondrogenic differentiation, as well as viscoelastic mechanical properties. This strategy paves the way to create in situ tissue engineered constructs via modular tissue engineering for therapeutic applications.